2021
DOI: 10.3389/fphar.2021.733387
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of SphK1 Inhibitors Based on Abnormal Expression of SphK1 in Inflammatory Immune Related-Diseases

Abstract: Sphingosine kinase 1(SphK1) a key enzyme that catalyzes the conversion of sphingosine (Sph) to sphingosine 1-phosphate (S1P), so as to maintain the dynamic balance of sphingolipid-rheostat in cells and participate in cell growth and death, proliferation and migration, vasoconstriction and remodeling, inflammation and metabolism. The normal expression of SphK1 maintains the balance of physiological and pathological states, which is reflected in the regulation of inflammatory factor secretion, immune response in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 159 publications
1
34
0
Order By: Relevance
“…Ppm1a has been shown to play a crucial role in the wound healing-inflammation-angiogenesis axis in mice 33 , and was down-regulated and hypermethylated 7 days after radiation but not later. Sphk1 plays a key role in the regulation of inflammatory responses 34 ; Sphkap , a modulator of Sphk1 , was up-regulated and hypermethylated in 1-month HLU + IR. The glycoprotein B4galt6 regulates astrocyte activation during CNS inflammation 35 and was up-regulated and hypomethylated .…”
Section: Discussionmentioning
confidence: 97%
“…Ppm1a has been shown to play a crucial role in the wound healing-inflammation-angiogenesis axis in mice 33 , and was down-regulated and hypermethylated 7 days after radiation but not later. Sphk1 plays a key role in the regulation of inflammatory responses 34 ; Sphkap , a modulator of Sphk1 , was up-regulated and hypermethylated in 1-month HLU + IR. The glycoprotein B4galt6 regulates astrocyte activation during CNS inflammation 35 and was up-regulated and hypomethylated .…”
Section: Discussionmentioning
confidence: 97%
“…Upregulation of SPHK1 expression may be linked to induction of a pro-survival, pro-inflammatory mechanism in short-term and long-term cultures upon exposure to Spike and P+S. SPHK1 is known to control cell survival, migration and inflammation [85] , [86] , and its deregulation has been observed in various inflammatory and immune related-diseases, such as hypertension, atherosclerosis, Alzheimer's disease, inflammatory bowel disease, rheumatoid arthritis, and asthma [87] , [88] , [89] . It is also known to regulate microglial phagocytosis [88] , and to modulate inflammation during cerebral ischemia/reperfusion injury [90] , [91] .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that TNF-α induced its effects on several aspects of placental function by activating SphK1 and identifies the S1P signaling pathway as a potential treatable target. However, since blocking SphK1 activity also inhibited trophoblast fusion [ 55 ] and since S1P has many diverse protective functions, the market-available SphK1 inhibitors [ 78 ] may pose off-target effects that will impact placental health and potentially fetal health through placental programming. Moreover, inhibition of SphK1 activity will reduce the synthesis of S1P which is protective and anti-apoptotic at normal levels [ 28 ].…”
Section: Discussionmentioning
confidence: 99%